A Comprehensive Study on Rural Housing in India: A Review - Abdul Ghaffar; Tejas H. Gajapure; Prachi S. Dhawle; Tirendra M. Meshram (International Journal of Rural and Regional Development, 2025)
Rural housing plays a pivotal role in the socio-economic development of India, as it directly influences the quality of life, health, and productivity of rural populations. Despite the launch of several governmental initiatives aimed at addressing rural housing shortages, a substantial segment of the rural population continues to reside in inadequate, unsafe, and non-durable dwellings that lack basic amenities. This paper presents a comprehensive review of the current scenario of rural housing in India, examining the key challenges such as affordability, accessibility, and the suitability of housing designs to local conditions. It evaluates major governmental schemes like the Pradhan Mantri Awas Yojana–Gramin (PMAY-G) and their impact on rural housing development, while also analyzing the implementation gaps and limitations. Furthermore, the paper explores the potential of sustainable and cost-effective construction technologies—such as the use of local materials, eco-friendly practices, and low-cost alternatives—that can be adapted to meet the specific needs of rural communities. The review seeks to offer valuable insights for researchers, policymakers, architects, and development practitioners committed to improving rural habitation by proposing holistic, inclusive, and context-sensitive solutions
Keywords: Affordable Housing; India; Pradhan Mantri Awas Yojana; Rural Development; Rural Housing; sustainable construction